SMOKING INFLUENCE ON THE OUTCOMES AND COMPLICATIONS OF CORONARY BYPASS SURGERY - P. K. Yablonsky; О. A. Sukhovskaya (Российский кардиологический журнал)
In the article, the analysis provided, of the literary data on smoking and smoking cessation influence on coronary bypass surgery efficacy and life duration of the patients. Most scientific articles provide data on the increase of both the mortality and complications number in smokers. Meta-analysis of 564 works on the influence of smoking on coronary bypass outcomes, convincing evidence was provided on the necessity to quit smoking. Ten, 20- and 30-year lasting observations post coronary bypass surgery demonstrate the benefits of smoking cessation for life duration increase in coronary heart disease. Meta-analysis of the various approaches efficacy in cardiovascular patients has been done in 2017 and shows the efficacy of medication therapy. Among the drugs for nicotin addiction treatment in cardiovascular patients, the most effective is varenicline, with confirmed safety in chronic stable cardiovascular disorders patients, as in acute coronary heart disease patients. To overcome the psychological component of the addiction it is worthy to conduct cognitive-behavioral therapy that can be done by the specialists of Call Center for smoking cessation organized by the Ministry of Health of Russian Federation.